Pengaruh Penggunaan Digital Payment QRIS dan Tingkat Literasi Digital terhadap Pendapatan Penjualan - Ariska , Ririn; Hendri, Nedi; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of the use of QRIS digital payments and the level of digital literacy on sales revenue in culinary sector MSMEs in East Metro City. The method used is quantitative with a survey approach, involving 65 respondents of MSME actors who use QRIS. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that the use of QRIS digital payments has a positive and significant effect on sales revenue. The ease and efficiency of transactions offered by QRIS allows MSMEs to reach more customers, especially among the younger generation who prefer digital payments. This study provides the importance of MSME development, especially in the use of digital technology to increase efficiency and revenue. Training and socialization programs are needed to improve digital literacy among MSME actors, in order to support wider acceptance and use of QRIS. Therefore, this study is expected to be a reference for related parties in formulating policies that support the digitalization of MSMEs in Indonesia.